Monitoring the Effect of Micro-oxygenation before Malolactic Fermentation on South African Pinotage Red Wine with Different Colour and Phenolic Analyses - Geldenhuys, L.; Oberholster, A.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2016)
The use of micro-oxygenation and its effect on the quality of the red wine varietal, Pinotage, is largely unknown. The influence of adding different oxygen dosages before malolactic fermentation on the phenolic composition and colour stabilisation of wine made from Pinotage was studied, and the suitability of certain spectrophotometric and RP-HPLC analyses to determine these changes were assessed in tanks of commercial lengths. Total oxygen dosages of 0 mg/L, 16 mg/L and 32 mg/L were applied, after which the wines underwent malolactic fermentation and maturation in the same tanks for two additional months. Decreases in anthocyanin concentration showed a strong inversely proportional correlation with increasing polymeric pigment concentration. This suggests that the addition of oxygen contributed to the early stabilisation of wine colour in Pinotage red wine. Overall, tannin concentrations were not significantly influenced by the oxygen treatments, although lower levels were observed in wines treated with oxygen. An important finding of the study was that there appeared to be little difference in the colour and phenolic composition of the wines between the 16 mg/L and 32 mg/L oxygen treatments. Good correlations were found between certain spectrophotometric techniques and the RP-HPLC analysis used to study changes induced by micro-oxygenation (total anthocyanins, total phenols). The colour and phenolic composition of Pinotage wine can be influenced before malolactic fermentation by micro-oxygenation. Some spectrophotometric phenolic analyses showed the same tendencies as observed with RP-HPLC (anthocyanins, monomeric flavan-3-ols, tannins), indicating their suitability to follow phenolic and colour changes induced by micro-oxygenation in Pinotage red wine.